PERANCANGAN PUSAT PELATIHAN DAN GALERI FOTOGRAFI DI KOTA BANJARBARU - Rivaldi Kurnia Bestari; Irwan Yudha Hadinata (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The growing interest in photography in South Kalimantan, particularly in Banjarbaru City, is evident from the increasing number of active photography communities in the area. This condition creates an opportunity for Banjarbaru to develop as one of the creative economy centers in the field of photography. Currently, photography learning facilities in Banjarbaru are still limited to short-term community workshops, while photography exhibitions are only held during certain events. Therefore, the Photography Training Center and Gallery in Banjarbaru is designed as a facility to accommodate both photography training and exhibition activities within an integrated building. The design applies a Modern Architecture approach, which emphasizes function as the foundation for shaping building forms (form follows function), while prioritizing simplicity, spatial efficiency, and organized layouts. Three main aspects are applied in this concept, including functional zoning, the use of minimalist and natural materials, and connectivity between spaces and buildings through comfortable transitional areas.